Renal dysfunction and podocyturia in pre-eclampsia may be explained by increased urinary VEGF. Issue 6 (5th May 2021) - Valsecchi, Luca; Galdini, Alessandro; Gabellini, Daniela; Dell'Antonio, Giacomo; Galbiati, Silvia; Fanecco, Andrea; Viganò, Ilaria; Smid, Maddalena; Bernardi, Rosa; Maestroni, Silvia; Baelde, Hans J; Zerbini, Gianpaolo
Abstract: Background: Pre-eclampsia has a major impact on renal function as shown by the development of proteinuria and podocyturia. How the systemic, soluble Fms-like tyrosine kinase-1 (sFlt-1)-driven inhibition of vascular endothelial growth factor (VEGF) activity detected in pre-eclampsia directly affects renal function remains unknown. The aim of the study was to clarify whether a non-canonical, renal-centred escape from VEGF inhibition in the case of pre-eclamptic pregnancy might have a direct impact on renal function. Methods: We evaluated plasma and urinary VEGF and placental growth factor (PlGF), plasma sFlt-1 and carbonic anhydrase IX (CAIX), albuminuria and podocyturia in 18 women with uncomplicated pregnancy, 21 with pre-eclampsia and 18 non-pregnant. The three groups were matched for age and the pregnant groups also for gestational age at enrolment. Results: Plasma VEGF was reduced in uncomplicated (P = 0.001) and pre-eclamptic (P = 0.0003) pregnancies when compared with controls. In uncomplicated pregnancy, the dysfunction was balanced by an increase (P = 0.009) of plasma PlGF. Increased (P = 0.0001) plasma CAIX in pre-eclampsia was in line with hypoxia. Pre-eclampsia resulted in a paradoxical increase (P = 0.0004) of urinary excretion of VEGF. Urinary concentrations of VEGF and podocytes were correlated to each other ( r 2 = 0.48, P < 0.0005) but also to plasma sFlt-1 ( r 2 = 0.56, P < 0.0001 and r 2 = 0.23, P = 0.03, respectively). Conclusions: In the case of pre-eclampsia, the systemic VEGF inhibition leads the kidney, possibly the podocyte, to increase the VEGF synthesis. The mechanisms leading to local VEGF overproduction or the overproduced VEGF itself are reasonably involved in the pathogenesis of podocyturia and, as a consequence, renal dysfunction in pre-eclampsia.